THU0008 A Negative High-Resolution Salivary Gland Ultrasound is Highly Predictive of Negative Labial Gland Biopsy in Patients with SICCA Symptoms. (10th June 2014) - Astorri, E.; Tappuni, A.; Sutcliffe, N.; Richards, P.; Pitzalis, C.; Bombardieri, M.
Abstract : Background: Sjögren's syndrome (SS) is a chronic autoimmune disease that affects salivary and lacrimal glands and results in xerostomia and xerophtalmia. Current criteria require the presence of either anti-Ro/La antibodies (ENA) or a positive focus score at labial salivary gland biopsy (LSGB) for SS classification [1]. Salivary gland biopsy is a highly specific marker for the diagnosis of SS but as an invasive procedure it is often indicated only in ENA- patients with sicca symptoms. Objectives: Here we investigated the capacity of high-resolution salivary gland ultrasound (US) to predict the result of a LSGB biopsy in a consecutive cohort of patient with sicca. Methods: Eighty-five consecutive patients attending the Combined Oral Medicine/Rheumatology SS Clinic at Barts and The London NHS Trust who underwent US and LSGB were recruited in the study. All patients displayed subjective and objective symptoms and signs of sicca. US imaging was scored as described by Salaffi et al. [2] while LSGB were scored following immunohistology, including CD3/CD20/CD138/CD21 markers [3]. US and LSGB were scored blindly with the radiologist and the pathologist unaware of the clinical data. Results: Of the 85 patients recruited, 36 fulfilled SS criteria (15 LSGB+ENA+, 16 LSGB+ENA−, 5 LSGB−ENA+) while 49 were classified as sicca (LSGB−ENA−). Within the whole cohort, abnormal US findings were observed in 34 patients, of these 29 displayed a positive LSGB. Concordance between US and LSGB was 91.76% (Kappa=0.826). Irrespectively of diagnosis and ENA status, the positive predictive value of having a positive LSGB with abnormal US findings was 85.29% whilst a negative US gave a negative LSGB predictive value of 96.08%. Conclusions: Our results demonstrate that high-resolution salivary gland US has a high concordance with LSGB. In particular, a negative US result is highly predictive of a negative labial gland biopsy in patients with sicca symptoms. These data suggests that, particularly in ENA− patients, the role of US is to guide whether or not LSGB is indicated, thus avoiding an invasive procedure in patients with an extremely low chance of a positive result. Thus, we propose that US should be considered in the SS diagnostic algorithm as a screening test before LSGB is performed. References: Vitali C, Bombardieri S, Jonsson R, Moutsopoulos HM, Alexander EL, Carsons SE, et al. Classification criteria for Sjogren's syndrome: a revised version of the European criteria proposed by the American-European Consensus Group. Ann Rheum Dis. 2002 Salaffi F, Carotti M, Iagnocco A, Luccioli F, Ramonda R, Sabatini E, et al. Ultrasonography of salivary glands in primary Sjogren's syndrome: a comparison with contrast sialography and scintigraphy. Rheumatology (Oxford). 2008 Barone F, Bombardieri M, Rosado MM, Morgan PR, Challacombe SJ, De Vita S, et al. CXCL13, CCL21, and CXCL12 expression in salivary glands of patients with Sjogren's syndrome and MALT lymphoma: association with reactive and malignant areas of lymphoid organization. J Immunol. 2008 Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3114